The Effects of Perioperative Intra-aortic Balloon Counter Pulsation on Left Ventricular Function in Patients Undergoing Coronary Revascularization Surgery - Sazzad, Md Faizus (Bangladesh Journals Online (JOL), 2019)
10.3329/bhj.v32i2.36095